Development of Online Learning System for Software Laboratory Center in Bina Nusantara University - Adrianto, Dennise; Martani, Marlene; Indriani, Danella; Susanti, Risan (Bina Nusantara University, 2017)
The purpose of this research was to produce a learning management system that could provide teaching materials and assessment tools for studentsso that they could improve their abilities and assess themselves. Using the waterfall Software Development Life Cycle (SDLC) model, the researchers divided the development into five phases. Those were analysis, design, implementation, testing, and maintenance. Analysis phase was done by conducting interviews and observations. The designing phase used Unified Modelling Language (UML), and implementation phase used PHP language with Model View Controller (MVC) framework CodeIgniter. Then, testing used eight golden rules and questionnaire as user acceptance test. In the end, this research could produce a Learning Management System (LMS) namely Online Learning System. It can deliver materials to students in BinaNusantara University. In addition, it helps students to find additional learning materials for the programming course, monitor, and assess their learning progress through the quiz and member dashboard.